Pengaruh Pemberian Motivasi terhadap Prestasi Belajar AUD dalam Education Golden Garden for Children - Titin Faridatun Nisa'; Farid Suhermanto (Universitas Trunojoyo Madura, 2014)
Education garden for golden children is an alternative to establish or provide a special learning club kids who are less or not being able to attend school. Objectives of this program are children of early age where the future is vital psychological time to prepare mentally before taking jejang higher education. Purpose of this study was to describe the effect of motivation on early childhood on academic achievement through a program education garden for golden children. Achievement of this study as a benchmark to see the readiness of preschool children into school. This research is qualitative research. The research was conducted in the village Kamal with a sample of preschool children are less able to number 26 children. Data collection techniques used test to see learning achievement and questionnaire to see the motivation to learn. Date were analyzed using descriptive quantitative. Based on results of the study showed that there was a significant effect of motivation on learningachievment in early childhood education garden for golden children with a correlation coefficient of 0,693.